Core outcome research measures in anal cancer (CORMAC): protocol for systematic review, qualitative interviews and Delphi survey to develop a core outcome set in anal cancer - Fish, Rebecca (BMJ Open, 2017)
INTRODUCTION: The incidence of anal squamous cell carcinoma (ASCC) has increased threefold in the last 30 years. Initial treatment is chemoradiotherapy, associated with short-term and long-term side effects. Future therapy innovations aim to reduce morbidity in treatment of early tumours while maintaining treatment efficacy, and to escalate treatment intensity in locally advanced tumours with acceptable quality of life (QoL). However, all phase III randomised controlled trials to-date have utilised different primary outcomes, which hinders evidence synthesis and presents challenges to the selection of optimal outcomes in future trials. No trial comprehensively assessed long-term side effects and QoL, suggesting outcomes reflecting issues important to patients are under-represented. This project aims to determine the priority outcomes for all stakeholders and reach agreement on a standardised core set of outcomes to be measured and reported on in all future ASCC trials. METHODS AND ANALYSIS: A systematic review will identify all outcomes reported in trials and observational studies of chemoradiotherapy as primary treatment for ASCC. Outcomes of importance to patients will be identified through patient interviews. The long list of outcomes generated from the systematic review and interviews will be used to create a two-round Delphi process, including key stakeholders (patients and healthcare professionals). The results of the Delphi will be discussed at a face-to-face consensus meeting. Discussion will focus on outcomes that did not achieve consensus through the Delphi process and conclude with anonymous voting to ratify the final core outcome set (COS). ETHICS AND DISSEMINATION: The final COS will feed directly into the PersonaLising Anal cancer radioTherapy dOse (PLATO) national anal cancer trials and the Association of coloproctologists of Great Britain and Ireland (ACPGBI) supported national anal cancer database. Utilisation of the COS will increase the relevance of research output to all stakeholders and increase the capacity for data synthesis between trials. This study has ethical approval and is registered with the Core Outcome Measures in Effectiveness Trials (COMET) initiative. TRIAL REGISTRATION NUMBER: PROSPERO registration ID: CRD42016036540